PENGARUH PENGENDALIAN INTERNAL DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN - Andri Susilo; Ariani Mulyasari (Sekolah Tinggi Ilmu Ekonomi La Tansa Mashiro, 2021)
This research is titled The Influence of Internal Control And Leadership Style on Employee Performance at PT. Primadelate Starlestari Malingping Branch. The purpose of this study is to find out if there is an influence between Internal Control and Leadership Style on Employee Performance at PT. Primadelate Starlestari Malingping Branch. The population used in this study is PT Employees. Primadelate Starlestari Malingping Branch as many as 51 respondents, where the population is also used as a sample. The phenomena that occur in this study are a decrease in sales, the difference in spare parts stock, and a minus of real stock in the H2 (spare parts) H3 (workshop) divisions.The sample technique used is Saturated Sample. Data collection techniques using observation, literature studies, questionnaires and documentation. Research instrument test using validity and reliability test. The data analysis technique uses a classic assumption test which consists of normality, multicolonierity, autocorrelation, and heteroskedastisity tests. Data analysis test in the form of multiple regression test, correlation, coefficient of determination. Then test the hypothesis using t test (partial) and F test (simultaneous). Based on the results of the data analysis, it can be concluded that partial internal control and leadership style have a positive and significant effect on employee performance. Then based on the results of the F test simultaneously internal control and leadership style simultasn affect the performance of employees at PT. Primadelate Starlestari Malingping Branch. It is hoped that this research can be used by companies as materials to minimize the risk of identified organizations or companies and improve employee performance.